1999
DOI: 10.1177/0146167299025005002
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Control through Counterfactual Thinking

Abstract: The control-gaining influence of counterfactual thought was examined in a month-long study of real-life exam performances. Participants were contacted immediately after receiving a test grade, the day before their next test, and right after receiving their second grade. Previous research has proposed that upward counterfactuals lead to improved future performance. The present study aimed to identify mediators of this process. Participants who generated more upward counterfactuals were predicted to perceive enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 24 publications
7
116
1
Order By: Relevance
“…To study the processing of explicitly provided comparisons, we need to posit a different cognitive mechanism (i.e., selectively attending to hypothesis confirming comparisons) and, by extension, different boundary conditions. In addition, whereas research on social comparisons (Huguet et al 2001) and counterfactual comparisons (Nasco and Marsh 1999) has argued that an increased willingness to imagine and search for upward comparisons tends to improve future performance, we argue that increased attention to unfavorable feedback can result in an underappreciation of the current choice and unnecessary switching to inferior alternatives. Finally, the explicit availability of the comparative feedback may not only change the underlying mechanism of the effect and its normative consequences, but it could possibly eliminate the effect of anticipated future choices altogether.…”
Section: Processing Multiple Price Comparisonsmentioning
confidence: 59%
“…To study the processing of explicitly provided comparisons, we need to posit a different cognitive mechanism (i.e., selectively attending to hypothesis confirming comparisons) and, by extension, different boundary conditions. In addition, whereas research on social comparisons (Huguet et al 2001) and counterfactual comparisons (Nasco and Marsh 1999) has argued that an increased willingness to imagine and search for upward comparisons tends to improve future performance, we argue that increased attention to unfavorable feedback can result in an underappreciation of the current choice and unnecessary switching to inferior alternatives. Finally, the explicit availability of the comparative feedback may not only change the underlying mechanism of the effect and its normative consequences, but it could possibly eliminate the effect of anticipated future choices altogether.…”
Section: Processing Multiple Price Comparisonsmentioning
confidence: 59%
“…Landman, Vandewater, Stewart, and Malley (1995) reported that upward counterfactual thinking among a sample of midlife women was associated with envisioning future changes in career, lifestyle, and interpersonal relationships. Nasco and Marsh (1999) tracked college students for a month, measuring their thoughts and reactions to exam scores, and then comparing these to their actual grades a month later. Immediately after receiving grades on a test early in the semester, students were asked to write down any counterfactual thoughts that came to mind.…”
Section: Counterfactuals Influence Behavior-mentioning
confidence: 99%
“…This represents a significant contribution because, as was mentioned earlier, prior counterfactual research has typically employed behavioral measures that are confined to the duration of the experimental session. The only other known study to take a longitudinal approach to assessing the effects of counterfactual thinking on individuals' actions and motivations is that of Nasco and Marsh (1999). Over the course of a month, the authors examined the influence of counterfactual thoughts on real-life exam performance.…”
Section: Discussionmentioning
confidence: 99%